PENGARUH PRINSIP-PRINSIP GOOD GOVERNANCE TERHADAP KUALITAS PELAYANAN PUBLIK DI KANTOR KECAMATAN SUKARAMI KOTA PALEMBANG - Holipah, Holipah (Jurnal Ilmiah Administrasi Dan Sosial, 2022)
Research title The influence of the principles of good governance on the quality of public services in the Sukarami Palembang District Office. Formulation of the problem How do the principles of good governance influence the quality of public services in the Sukarami District Office, Palembang City. The purpose of this study was to analyze the effect of the principles of good governance on the quality of public services in the Sukarami District Office, Palembang City. The research method uses quantitative, the methods used are observation, questionnaires, and documentation. The sample in this study is the community that proposes services in the Sukarami sub-district. The analysis technique used is to use a simple regression formula. Based on the results of the research and discussion that the influence of the principles of good governance on public services in Sukarami District, Palembang. The population in this study were 225 respondents, namely people who received services at the Sukarami Palembang sub-district office, from testing the hypothesis the value obtained was 0.56 or 18.4%. from simple regression calculations with an error rate of 0.05, namely 0.000 0.05. While the correlation test for the determinant of the value obtained (R) is 753. From the output it is obtained (R Square) of 0.567 which implies that the effect of the principle variable of Good Governance (X) on service quality (Y) is 56.7%, the remaining 43.3% does not affect the variable. In this case, the evidence of this research has shown that strong good governance principles contribute to good service quality. Keywords: Good governance principles, Public Service